Pengukuran Maturitas Tata Kelola Teknologi Informasi Pada Universitas Kanjuruhan Malang Menggunakan Kerangka Kerja COBIT 4.1 Domain Plan and Organise dan Acquire and Implement - Simson Hasian Pangaribuan; Suprapto Suprapto; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Universitas Kanjuruhan Malang is an educational institute that implements information technology in conducting business process activities. Utilization of information technology requires support from appropriate governance. Manajemen Sistem Informasi is the unit that responsible for handling the management of information technology in the campus environment. The results obtained from the distribution of questionnaire, interview and observation on the unit show that there are problems related to the planning and procurement of information technology. Due to this situation, an evaluation of information of technology management is required to find the solution to these problems. The evaluation is done using the COBIT 4.1 framework that focuses on the Plan and Organize and Acquire and Implement domains. The selection of these framework and domains is based on existing issues and COBIT 4.1 can assist institute in measuring the extent of maturity of information technology governance. Then analysis to the level of maturity that already obtained. The results show that the maturity level of the Plan and Organise domain is 1.8 and the Acquire and Implement domain is 1.0. Measurement results of maturity level is a reference in making recommendations. Recommendations are expected to assist Universitas Kanjuruhan Malang in improving technology governance to achieve the expected maturity targets. One of the recommendation is to improve the document of information technology strategic plan.